THE RELATIONSHIP BETWEEN LEARNING MOTIVATION AND STUDENTS’ ENGLISH LEARNING ACHIEVEMENTS OF STAHN GDE PUDJA MATARAM - Gede Eka Puja Dyatmika (Yavana Bhasha : Journal of English Language Education, 2022)
This study aims to find a relationship between learning motivation and Students’ English learning achievement of STAHN Gde Pudja Mataram. This research is an ex post facto research using correlation analysis. Ex post facto research is research that examines causal relationships that are not manipulated or treated (designed and implemented) by the researcher. Research data were collected using questionnaires and tests. Data were analyzed using product moment correlation analysis. The conclusion of this study is: there is a positive and significant relationship between learning motivation and students’ English learning achievement of STAHN Gde Pudja Mataram.